2023
DOI: 10.3390/life13051087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Genes Associated with Flooding Tolerance in Mulberry Plants

Abstract: Mulberry (Morus alba), a widely distributed economic plant, can withstand long-term flooding stress. However, the regulatory gene network underlying this tolerance is unknown. In the present study, mulberry plants were subjected to submergence stress. Subsequently, mulberry leaves were collected to perform quantitative reverse-transcription PCR (qRT-PCR) and transcriptome analysis. Genes encoding ascorbate peroxidase and glutathione S-transferase were significantly upregulated after submergence stress, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…This was corroborated by a transcriptome analysis that revealed the up-regulation of genes associated with ethylene biosynthesis in submerged roots [16,49]. Hu et al [50] reported forty differentially expressed genes involved in ethylene signaling in mulberry plants under waterlogging. This finding emphasizes the important role of phytohormones in modulating the signaling networks that respond to waterlogging in plants.…”
Section: Wt Line Maintained Cellular Membrane Integrity and Exhibited...mentioning
confidence: 79%
“…This was corroborated by a transcriptome analysis that revealed the up-regulation of genes associated with ethylene biosynthesis in submerged roots [16,49]. Hu et al [50] reported forty differentially expressed genes involved in ethylene signaling in mulberry plants under waterlogging. This finding emphasizes the important role of phytohormones in modulating the signaling networks that respond to waterlogging in plants.…”
Section: Wt Line Maintained Cellular Membrane Integrity and Exhibited...mentioning
confidence: 79%
“…The localized QTLs were mainly concentrated in linkage groups 4, 6, 8, 10, and 11, which is consistent with some previous studies [ 33 , 53 , 54 ]. Transcriptome analysis has been used to study the response of many plant species to various environmental stresses [ 55 , 56 , 57 , 58 , 59 ]. With the development of high-throughput sequencing technology and the continuous improvement of transcriptome databases, the combination of transcriptome data with traditional QTL mapping or GWAS has been widely used in the prediction of candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional studies have partially revealed the mechanism of hypoxia-induced transcriptional and translational regulation in plants [18]. A study of Morus alba showed that genes associated with cytokinin, ethylene, and MAPK signaling were significantly upregulated under flooding treatment [19]. Another study focused on Salix matsudana, which overexpressed SmTTF30 and enhanced its tolerance to flooding stress by increasing peroxidase activity and reducing malondialdehyde content [20].…”
Section: Introductionmentioning
confidence: 99%